Strategi Dosen Mengembangkan Media Pembelajaran Berbasis Teknologi Informasi Untuk Meningkatkan Keterampilan Berfikir Kritis Mahasiswa PAI IAIN Curup - Wanto, Deri; Sendi, Okni Aisa Mutiara (Jurnal Penelitian, 2022)
The development of this increasingly advanced era requires educators to have new innovations in the use of Information Technology-based media in directing more interesting and conducive learning in the implementation of learning. The purpose of this study was to find out how the lecturer's strategy in developing information technology-based learning media to improve critical thinking skills of PAI IAIN Curup students. This study uses a qualitative approach, for data analysis using qualitative data analysis methods, the technique used is non-statistical data techniques. Data were collected from interviews, observations and documentation. This study found that the lecturer's strategy in developing information technology-based learning media to improve the critical thinking process of PAI IAIN Curup students was by independent learning, assignments, product creation and field research. In the use of IT learning media, the IT media used are computers or laptops, LCD projectors and then the use of applications such as Mindemaple, Mind Master, Kahoot, Canva, Videoscrabe, Mandele, Zotero, Spss, QR Code, Kinemaster, Flip PDF Professional. Supporting factors are the availability of wifi, available media applications that will be used. Then the factors that hinder the lack of student learning facilities.